Financing Energy Efficiency in Developing Countries--Lessons Learned and Remaining Challenges - Sarkar, Ashok (2012)
Although energy efficiency implementation is increasingly being recognized by policymakers worldwide as one of the most effective means to mitigating rising energy prices, tackling potential environmental risks, and enhancing energy security, mainstreaming its financing in developing country markets continues to be a challenge. Experience shows that converting cost-effective energy savings potential, particularly the demand-side improvement opportunities across sectors, into investments face many barriers and unforeseen transaction costs. This paper draws upon selected experiences with financing energy efficiency in developing countries to explore the key factors of various programmatic approaches and financing instruments that have been applied successfully for delivering energy efficiency solutions. Through case studies, a diverse range of institutional issues are examined related to the identification, packaging, designing, and monitoring approaches that have been used to catalyze traditional and innovative financing of energy efficiency projects. With adequate liquidity in major developing country markets and availability of modern energy savings technologies, it is often the institutional issues that become a key challenge to address in order to finance and implement robust programs. As further operational experience is gained, increased knowledge sharing can lead to scaling-up of such energy efficiency investments. The paper concludes with some ideas for accelerating implementation.